Managing bureaucratic reputation in the face of crises: An experimental examination of the effect of strategic communication. (Public Administration Review, 2022)
Research on bureaucratic reputation has found that public organizations respond strategically to reputational threats. To understand better the way public organizations should communicate with their external audiences, upon which they depend for necessary resources and democratic legitimacy, this study examines the effectiveness of various communication strategies that agencies often use in response to a crisis. The results of a series of vignette experiments involving US adults show that an agency's communication strategy in response to crises does indeed influence citizens' reputation judgments. Specifically, compared with remaining silent, organizations that offer the public explanations of crises mitigate their reputational losses more effectively. Further, this study finds that people's prior reputation judgments and the nature of the crisis itself are important factors involved in the formation of reputation judgments, although these findings contradict communication theories. The implications for theory and practice are discussed.